Effect Of Financial Literacy On Financial Management Of Smes In Building An Ectourism-Based Coffee Village In Mekarbuana Village, Tegalwaru District, Karawang District - Ery Rosmawati; Wike Pertiwi; Dini Yani; Zenita Apriani (Program Studi Administrasi Bisnis, 2023)
One of the villages in South Karawang, which is located at the foot of Mount Sanggabuana, has a very high natural tourism potential, with a distance between the village and the city center of around 45.30 km. The demographic location which is quite far from the City Center coupled with post-pandemic conditions means that people's income is still below average and has even decreased. Financial management is one of the main problems in MSMEs because many ignore the importance of financial literacy.This is in line with the results of the National Financial Literacy and Inclusion Survey (SNLIK) conducted by the Financial Services Authority (OJK) in 2019 which shows that both in terms of understanding and use of financial products/services, people in rural areas are still quite behind compared to the rest of the population. who live in the city area. This research was conducted to determine the effect of financial literacy on financial management. The method used in this research is quantitative research. Based on the results of research with the help of SPSS version 26, it is known that the R square is 0.373. Which means bthat the variable financial literacy affects financial management 37.3% and the remaining 62.7 is influenced by other factors. The results of the calculation of the t test show that t count is greater than t table (4.084 > 2.048) so it can be concluded that there is a significant influence between financial literacy and financial management in MSMEs in Mekarbuana Village.